EFFECT OF THE GABA DERIVATIVE SUCCICARD ON THE LIPID AND CARBOHYDRATE METABOLISM IN THE OFFSPRING OF RATS WITH EXPERIMENTAL PREECLAMPSIA IN EARLY AND LATE ONTOGENY - E. A. Muzyko; V. N. Perfilova; A. A. Nesterova; K. V. Suvorin; I. N. Tyurenkov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
Maternal preeclampsia can bring about metabolic disorders in the offspring at different stages of ontogeny. Up to date, no ways of preventive pharmacological correction of lipid and carbohydrate metabolism disorders developing in different periods of ontogeny in the children born to mothers with this pregnancy complication, have been developed.The aim of the experiment was to study the effect of the gamma-aminobutyric acid derivative succicard (22 mg/kg) and its reference drug pantogam (50 mg) administered per os in the course of treatment in puberty (from 40 to 70 days after birth), on the parameters of lipid and carbohydrate metabolism in the offspring of the rats with experimental preeclampsia, in different periods of ontogeny.Materials and methods. To assess the activity of lipid and carbohydrate metabolism in the offspring, an oral glucose tolerance test was performed at 40 days, 3, 6, 12 and 18 months of age. The level of glycosylated hemoglobin was measured at the age of 6, 12, and 18 months, and the concentrations of total cholesterol, high-density lipoprotein cholesterol and triglycerides were tested at 40 days, 3, 6, 12, and 18 months of age.Results. The offspring of the rats with experimental preeclampsia, were found out to have lipid and carbohydrate metabolism disturbances during early (40 days and 3 months of age) and late (6, 12, and 18 months of age) ontogeny. In comparison with the offspring of healthy females, these disturbances were manifested by significantly higher levels of glucose revealed during the oral glucose tolerance test, by high glycosylated hemoglobin in males, and with elevated concentration of total cholesterol and triglycerides and a low level of high-density lipoprotein cholesterol in the negative control rats. Both the gamma-aminobutyric acid derivative succicard and its reference drug pantogam, reduced the negative effect of experimental preeclampsia on lipid and carbohydrate metabolism in the offspring in late ontogeny (6, 12 and 18 months of age). The effectiveness of succicard was either higher or comparable with pantogam.Conclusion. Thus, the negative impact manifestations of experimental preeclampsia on lipid and carbohydrate metabolism, are revealed in the offspring in early (40 days and 3 months) and late (6, 12 and 18 months of age) ontogeny. The gamma-aminobutyric acid derivative succicard reduces the negative effect of experimental preeclampsia. Based on this finding, the drug implies the possibility of the development of a safe and highly effective medicine for preventive correction of lipid and carbohydrate metabolism disorders in the children born to mothers with preeclampsia.